Pendidikan Kesehatan dan Latihan Batuk Efektif pada Penderita Tuberkulosis Paru dengan Bersihan Jalan Napas Tidak Efektif di Wilayah Puskesmas Mulyorejo - Ikhfana Syafina (Medan Resource Center, 2026)
Tuberculosis (TB) remains a major public health issue in Indonesia, with ineffective airway clearance being a common clinical manifestation due to excessive sputum production. This study aims to analyze the effect of health education and effective coughing exercises on pulmonary TB patients with ineffective airway clearance in the working area of the Mulyorejo Health Center. This research employed a descriptive case study method involving three subjects. The intervention was carried out over three consecutive days through education, demonstration, and re-demonstration of effective coughing techniques. The evaluation focused on indicators of airway clearance, including the ability to expel sputum, respiratory rate, the presence of ronchi, dyspnea level, and breathing patterns. The results showed significant improvements in all indicators. Patients were able to expel secretions more smoothly, respiratory frequency decreased to normal limits, ronchi disappeared, dyspnea reduced, and breathing patterns became regular. In conclusion, the integration of health education and effective coughing exercises effectively resolves the problem of ineffective airway clearance and empowers patients to perform independent self-care at home.